FORWARD CHAINING DALAM DIAGNOSIS PENYAKIT TUMBUHAN ALLIUM CEPA VAR AGGREGATUM - Dine Tiara Kusuma; Sely Karmila; Tiara Amalia Nova (Sekolah Tinggi Teknik - PLN, 2018)
The agriculture department of Solok West Sumatra district especially Agricultural Extension Agency (BPP) of Lembang Jaya Sub-district, has decreased the productivity of onion every year. This plant has decreased because it often attacked by pests or diseases, and lack of knowledge about the symptoms of onion’s pests or diseases. To fix this problem, made an application to facilitate the farmers, to know the type of pest or disease from symptoms on the onion and solution of each type of diseases. The method used is Forward Chaining. Forward Chaining Method is collection of data from each symptom that appear on the Allium Cepa Var Aggregatum. Then, made a decision to get the results about the solution and type of disease on the Allium Cepa Var Aggregatum. The results of this study is to show the type of disease and solution that has been detected based on symptoms on the Allium Cepa Var Aggregatum.